Mixed feelings: Unintended consequences of HIV outreach care in Zimbabwe - Noa Gluskinos; Caroline Maposhere; Ushehwedu Kufakurinani; Godfrey Hove; Kathy McCarty; David Katzenstein; Anat Rosenthal (PLoS ONE, 2026)
Background Decentralization of antiretroviral therapy (ART) brought treatment to millions of people in Sub-Saharan Africa. However, the implications of such decentralization are still not fully understood. Methods The study included 60 semi-structured interviews with community leaders, healthcare providers, patients, and community members served by a rural mission hospital in Zimbabwe, conducted in January-March 2019. Interviews were transcribed and translated into English and coded using an iterative codebook. Coded extracts were grouped into themes and categories, systematically using QDA Miner qualitative analysis software. Findings The study reveals that treatment-for-all policies and decentralization of ART have indeed improved access to care (as experienced by the study participants). However, the study shows that these policies also had unintended negative consequences. Stigma and complex social relations significantly affect the practices and experiences of ART outreach care, for both patients and healthcare providers, and may hamper attempts to reduce stigma as well as increase physical and social barriers to accessing ART. Conclusions The study’s results highlight the need to understand the consequences of the decentralization of HIV care, as well as the barriers and facilitators associated with ART outreach in order to improve quality of care and provide true accessibility to HIV care for all.